A developmental perspective on decision making in young soccer players: The role of executive functions - Heisler, S. M.; Lobinger, B. H.; Musculus, L. (Psychology of Sport and Exercise, 2023)
Lately, interest in both domain-specific and domain-general cognitive processes has increased as a means to explain soccer player expertise. While the two types of processes have mostly been studied separately, we sought to connect these lines of research by investigating the role of executive functions in soccer players` decision making from a developmental perspective. As these cognitive processes as well as their relation might differ between age groups, we took a developmental perspective to better understand this link in a sample of N = 128 soccer players (Mage = 10.69 years, SD = 1.44). Two age groups (younger vs. older players) performed a video-based option-generation and decision-making task that used temporal occlusion. Additionally, executive functions were assessed with standardized computer-based tests. Results show a link between executive functions and sport-specific decision making, most prominent for working memory. Further, older players generated better options and showed better inhibition and cognitive flexibility than younger players. We suggest there is a crucial turning point in cognitive development around the age of 11 years.